Pediatric rehabilitation : principles and practice - Alexander, Michael A. (Michael Allen), 1947-; Matthews, Dennis J. (Demos Medical, 2010)
Pediatric Rehabilitation: Principles and Practice is the classic comprehensive reference on pediatric rehabilitation. Taking the reins from Dr. Gabriella Molnar, Drs. Michael Alexander and Dennis Matthews have brought together a broad range of pediatric specialists to thoroughly update the text to reflect current thinking and practice. The Fourth Edition covers everything from basic examination and psychological assessment to electrodiagnosis, therapeutic exercise, orthotics and assistive devices, and in-depth clinical management of the full range of disabling childhood diseases and injuries.